Impacts of seasonal variation and operating parameters on double-stage trommel performance. (1st March 2019) - Ashkiki, Alireza Rajabpour; Felske, Christian; McCartney, Daryl
Highlights: Material composition by particle size of co-mingled MSW. Seasonal differences in organic waste material properties in a northern climate. Seasonal differences in double-stage trommel screen performance. Effect of feed rate on double-stage trommel screen performance. Trommel clogging correlated to freeze-thaw exposure of organic material. Abstract: The high-level objective of this research was to quantify and assess impact of uncertainties of trommel screening with respect to feed-rate variation, clogging of screen apertures, and seasonal variation in waste characteristics, including particle size distribution (PSD) and composition using full-scale trials. A two-stage trommel screen which is operated at a municipal solid waste processing facility located in a cold region (Edmonton, Canada) was evaluated. The waste processed was co-mingled refuse with the recyclable material removed. The variation of size separation mass balance and recovery with respect to total and overs loading feed rate, season and operation time were monitored. The characteristics of the feedstock and separated waste streams were determined by sieve and compositional analyses. Separation and recovery results verified that the performance of the first stage where <5 cm of organic-rich waste was screened out, varied seasonally. Further, a strong linear correlation was obtained between recovery results and corresponding overs loading rate that varied between seasons. This correlation also varied within operation cycle during the winter trials due to clogging of screens. An equation is proposed to quantify clogging formation according to operation uptime and feed rate. Waste characterization results indicated the waste generated in the winter, spring, and summer had three distinct PSDs, especially the compostable fraction, contributing to the seasonality in trommel performance. In contrast, the PSD of the combustible fraction remained consistent in all seasons. This research successfully quantified the impact of uncertainties of full trommel operations in different seasons and during the operation cycle.